The Effects of Medical Well Baby Visits in Promoting Earlier First Dental Visits for Children. (January 2018) - Park, S.; Momany, E.T.; Jones, M.P.; Kuthy, R.A.; Askelson, N.M.; Wehby, G.L.; Damiano, P.C.; Chi, D.L.
The objective of the study was to assess the effects of medical well baby visits in promoting earlier first dental visits. We analyzed Iowa Medicaid claims data (2000–2013). The sample included 4 cohorts of children born in 2000, 2003, 2007, or 2010 and enrolled in Medicaid from birth ( N = 38, 211). Children were followed for 3 y. The independent variables were cohort year and medical well baby visit frequency during 3 time periods (birth to age 10 mo, ages 11–19 mo, ages 20–36 mo). We used survival analyses to estimate first dental visit rates. First dental visit rates improved significantly from 2000 to 2013, with children in latter cohorts having significantly earlier first dental visits. Children with more medical well baby visits before age 11 mo had significantly delayed first dental visit rates than children with fewer medical well baby visits. The opposite was observed for children with more medical well baby visits between ages 11 to 19 mo and ages 20 to 36 mo. First dental visit rates for Medicaid-enrolled children have improved, but there continues to be a need for early interventions to improve age 1 dental visits and other preventive oral health behaviors. Knowledge Transfer Statement: The results of this study can be used by policy makers when developing strategies to improve access to dental care for young children in Medicaid. With consideration to promoting earlier preventive dental visits for publicly insured children, this study could lead to early interventions and improved health outcomes.